Anthropocentrism: A Comparative Study of Hemingway and Faulkner’s Perception on Human-Nature Relationship - Gaman, Alexander Paruda (Proceedings of English Linguistics and Literature, 2024)
From the early-to-mid 20th century, the environmental issues portrayed in literature changed human environmental awareness and attitudes toward nature worldwide. Hemingway’s The Short Happy Life of Francis Macomber and Faulkner’s The Bear depicts the connection between man and nature and how the characters’ attitudes and actions affect the environment. This study aims to compare and contrast the portrayals of the relationship between man and nature in both stories and how the authors’ perception of the relationship differs. By utilizing a framework of anthropocentrism, this paper will analyze how the characters’ actions and attitudes towards nature represent the authors’ perceptions of the human-nature relationship. Hemingway’s story represents the exploitative attitude of hunting wild animals, while Faulkner’s story portrays a deep and respectful connection with nature, thus rejecting the idea of anthropocentrism. These different findings reflect the authors’ contrasting perceptions of the relationship between man and the natural world, formed by their experiences and backgrounds. Hemingway’s depiction of exploitative hunting reflects his adventurous experience on the African safari, while Faulkner’s portrayal of interconnection with nature resembles his connection to the southern rural wilderness of Mississippi. The contrasting perceptions show that the authors’ backgrounds play an important role in developing their perspectives and values of human-nature relationships, affecting the way they present different viewpoints and themes in their work